Endogenous Cellular MicroRNAs Mediate Antiviral Defense against Influenza A Virus - Shanxin Peng; Jing Wang; Songtao Wei; Changfei Li; Kai Zhou; Jun Hu; Xin Ye; Jinghua Yan; Wenjun Liu; George F. Gao; Min Fang; Songdong Meng (Elsevier, 2018)
The reciprocal interaction between influenza virus and host microRNAs (miRNAs) has been implicated in the regulation of viral replication and host tropism. However, the global roles of the cellular miRNA repertoire and the mechanisms of miRNA-mediated antiviral defense await further elucidation. In this study, we systematically screened 297 cellular miRNAs from human and mouse epithelial cells and identified five inhibitory miRNAs that efficiently inhibited influenza virus replication in vitro and in vivo. Among these miRNAs, hsa-mir-127-3p, hsa-mir-486-5p, hsa-mir-593-5p, and mmu-mir-487b-5p were found to target at least one viral gene segment of both the human seasonal influenza H3N2 and the attenuated PR8 (H1N1) virus, whereas hsa-miR-1-3p inhibited viral replication by targeting the supportive host factor ATP6V1A. Moreover, the number of miRNA binding sites in viral RNA segments was positively associated with the activity of host miRNA-induced antiviral defense. Treatment with a combination of the five miRNAs through agomir delivery pronouncedly suppressed viral replication and effectively improved protection against lethal challenge with PR8 in mice. These data suggest that the highly expressed miRNAs in respiratory epithelial cells elicit effective antiviral defenses against influenza A viruses and will be useful for designing miRNA-based therapies against viral infection.